Detrial Apatite and Zircon dating of the Stac Fada Member and wider Stoer Group, northwest Scotland - Kenny, Gavin; O'Sullivan, Gary J; Alexander, Stephen; Simms, Michael; Chew, David M; Kamber, Balz S (Supplement to: Kenny, G et al. (2019): On the track of a Scottish impact structure: a detrital zircon and apatite provenance study of the Stac Fada Member and wider Stoer Group, NW Scotland. Geological Magazine, 156(11), 1863-1876, https://doi.org/10.1017/S0016756819000220, 2018)
Full zircon and apatite data for: On the track of a Scottish impact structure: a detrital zircon and apatite provenance study of the Stac Fada Member and wider Stoer Group, northwest Scotland.